Empowerment of Bamboo Weaving Crafts by Women Farmers Group Dana Mertha Mesari, Kayubihi Village - Putra, I Gst. B. Ngr. P.; Jayawarsa, Anak Agung Ketut; Maharani, Ida Ayu Dinda Priyanka (MOVE: Journal of Community Service and Engagement, 2024)
Bamboo woven craft artisans in Kayubihi Village, especially Banjar Bangklet-Kayang, come from mothers, especially those who work as farmers. The problems faced by partners include: 1) Bookkeeping is still done conventionally so that it is less effective and efficient; 2) Distribution and marketing of products are carried out traditionally so that the scope of the product market share is still minimal; 3) the availability of facilities and infrastructure, raw materials, and auxiliary materials has reached the end of its economic life. The solutions offered to this problem are 1) Financial Transaction Recording Training and Provision of a Digitalized Financial Recording System; 2) Provision of a Website as a Form of Marketing Strategy and Online Marketing Strategy Training; 3) Provision of Production Supporting Facilities and Infrastructure.